Epidemiology and treatment of multiple sclerosis in elderly populations - Vaughn, Caila B; Jakimovski, Dejan; Kavak, Katelyn S; Ramanathan, Murali; Benedict, Ralph H B; Zivadinov, Robert; Weinstock-Guttman, Bianca (Nature reviews. Neurology, 2019)
The prevalence of multiple sclerosis (MS) and the age of affected patients are increasing owing to increased longevity of the general population and the availability of effective disease-modifying therapies. However, ageing presents unique challenges in patients with MS largely as a result of their increased frequency of age-related and MS-related comorbidities as well as transition of the disease course from an inflammatory to a neurodegenerative phenotype. Immunosenescence (the weakening of the immune system associated with natural ageing) might be at least partly responsible for this transition, which further complicates disease management. Currently approved therapies for MS are effective in preventing relapse but are not as effective in preventing the accumulation of disability associated with ageing and disease progression. Thus, ageing patients with MS represent a uniquely challenging population that is currently underserved by existing therapeutic regimens. This Review focuses on the epidemiology of MS in ageing patients. Unique considerations relevant to this population are discussed, including the immunology and pathobiology of the complex relationship between ageing and MS, the safety and efficacy of disease-modifying therapies, when discontinuation of treatment might be appropriate and the important role of approaches to support wellness and cognition.